2022
DOI: 10.1108/jeas-03-2022-0073
|View full text |Cite
|
Sign up to set email alerts
|

ICT diffusion, women empowerment, and sustainable development in SAARC countries

Abstract: PurposeThe main purpose of this paper is to analyze the role of information and communication technology (ICT) diffusion in women empowerment and in fostering the process of achieving the Sustainable Development Goals (SDGs) in South Asian Association for Regional Cooperation (SAARC) countries using panel data from 2005 to 2020.Design/methodology/approachAn ICT diffusion index was constructed using principal component analysis (PCA). Further, the study uses econometric techniques robust to cross-sectional depe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…To examine the research hypothesis and enhance methodological transparency, the study follows Aguinis et al (2018) and adopts a panel data sample covering the annual data of 88 developing countries from 2005 to 2019. The variables include the per capita real gross domestic product (GDP) constant at 2010 United States (US)$ (GDP), which measures economic growth; the financial development index (FD) based on Svirydzenka (2016), which evaluates financial sector development on several dimensions; and ICT diffusion proxied by ICT diffusion index (Pradhan et al, 2020;Verma et al, 2022). In addition, the study employs principal component analysis (PCA) to establish an ICT diffusion index, which includes fixed telephone subscription (per 100 individuals), mobile cellular subscription (per 100 individuals), fixed broadband subscription (per 100 individuals) and percentage of individuals using the Internet.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To examine the research hypothesis and enhance methodological transparency, the study follows Aguinis et al (2018) and adopts a panel data sample covering the annual data of 88 developing countries from 2005 to 2019. The variables include the per capita real gross domestic product (GDP) constant at 2010 United States (US)$ (GDP), which measures economic growth; the financial development index (FD) based on Svirydzenka (2016), which evaluates financial sector development on several dimensions; and ICT diffusion proxied by ICT diffusion index (Pradhan et al, 2020;Verma et al, 2022). In addition, the study employs principal component analysis (PCA) to establish an ICT diffusion index, which includes fixed telephone subscription (per 100 individuals), mobile cellular subscription (per 100 individuals), fixed broadband subscription (per 100 individuals) and percentage of individuals using the Internet.…”
Section: Methodsmentioning
confidence: 99%
“…The variables include the per capita real gross domestic product (GDP) constant at 2010 United States (US)$ (GDP), which measures economic growth; the financial development index (FD) based on Svirydzenka (2016), which evaluates financial sector development on several dimensions; and ICT diffusion proxied by ICT diffusion index (Pradhan et al. , 2020; Verma et al. , 2022).…”
Section: Methodsmentioning
confidence: 99%
“…The first grouping pertains to research on women and ecological problem-solving (Nastabilla, Prakoso, & Alhafizh, 2022;Prakash, Mcglade, Roxy, & Roy, 2022;Srinath, 2008), with some studies even using the term "green social work". The second grouping focuses on research related to women's empowerment in the context of sustainable development, and it has found that there is a significant contribution to achieving sustainable development goals (Aluko & Okuwa, 2018;AMAECHI, 2019;Verma, Giri, & Debata, 2022) when carried out through women's empowerment. The novelty in this research lies in the specificity of the region, as women's empowerment contributing to sustainable development goals in this study is conducted in coastal areas.…”
Section: Empowerment Of Coastal Women and Their Contribution To Envir...mentioning
confidence: 99%
“…Having a well-founded ICT penetration and access can help improve gender equality in a variety of ways, laying the groundwork for gender-inclusive policy and planning. ICT can be a valuable resource for women's empowerment, particularly in the economic sphere (Verma et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%